Deconstructing overhearing viewers: TVmojis as story retellers. Issue 2 (3rd April 2018) - Cui, Xi
Abstract : The TVmoji is a pictorial visual device that captions or interprets television footage. It is widely used in many non-scripted television shows, particularly in East Asia. Using a Goffmanian footing analysis, this study categorizes TVmojis as blurted expressions, soliloquies, captions, narration, fictive viewer's talkbacks, and fictive viewer's comments. The author argues that by playing various roles, TVmojis help construct the viewer's sense of being a bystander while concealing the producers' manipulations of the media's interactive roles vis-à-vis the viewers. The author contends that to improve the understanding of this editorial manipulation-in-disguise, the media should be conceptualized as retellers, rather than representers, of narrative using footage and visual devices such as TVmojis.